„Tęczowa zaraza” a niezależność Kościoła i godność człowieka. Uwagi do wyroku Sądu Okręgowego w Krakowie z 8 grudnia 2020 r., sygn. I C 1357/19 - Borecki, Paweł (Studia Prawa Publicznego, 2021)
In the judgment of 8 December 2020 (file reference number I C 1357/19), the District Court in Kraków dismissed the action for infringement of personal rights and payment against the Archbishop of Kraków. M. Jędraszewski. The reason was his statement during the homily on August 1, 2019 about the threat of a “rainbow plague”. The court found that the statement did not infringe the personal rights of the petitioner. However, it had an objectively insulting and defamatory nature towards LGBT people. It violated their dignity. The court found that the defendant did not act illegally. He referred to the provisions of the Concordat of July 29, 1993. The action of the Archbishop. M. Jędraszewski exceeded the limits of religious freedom. The statement violated the principles of social coexistence. However, the court did not pay heed to his, nor did it keep an equal distance between the parties in the dispute. It expressed the traditional axiology and vision of social life. The only valid argument for dismissing the claim was that the defendant’s statement was not addressed specifically to the claimant.